Kajian Biaya Replanting Karet (Havea brasiliensis) Kebun Masyarakat Menggunakan Mesin Pertanian (Chainsaw) Di Kabupaten Padang Lawas - Hasibuan, Surtan; Manik, Marino; Lubis, Anita Rizky; Gea, Sary Indah Yani (Jurnal Kridatama Sains dan Teknologi, 2024)
Rubber Replanting is the cutting down or cutting of unproductive rubber trees, renewing old plants and replacing the plants with more productive plants. In general, rubber plant rejuvenation is carried out when the plant reaches the age of 25-30 years. However, in this study, rejuvenation was carried out on 14-year-old rubber plants. This research was conducted to determine the cost of cutting down rubber trees independently in an area of 1 Ha, and utilizing tree waste into useful firewood. This research was conducted from September 30 to October 12, 2024 with a research area of 1 hectare. The cost of replanting using heavy equipment generally costs 10 - 15 million in 1 Ha. This information was obtained from direct interviews with business actors who provide heavy equipment rental services in the form of excavators in the Padang Lawas area. Based on the economic ability of rubber plantation farmers, using Chainsaw machine tools is estimated to be more economical than using heavy equipment such as excavators. How to replant rubber by cutting rubber trees one by one and chopping trees into firewood. Analysis using Descriptive analysis and secondary data. The results showed that replanting using chainsaw is more economical than using heavy equipment (Excavators) and rubber trees that are uprooted can be of economic value and this research can be a reference for farmers who want to do replanting